Risk of Post-stroke Epilepsy Following Stroke-Associated Acute Symptomatic Seizures - Lin, Ru; Yu, Yaoyao; Wang, Yi; Foster, Emma; Kwan, Patrick; Lin, Mengqi; Xia, Niange; Xu, Huiqin; Xie, Chenglong; Yang, Yunjun; Wang, Xinshi (Frontiers in Aging Neuroscience, 2021)
Abstract Objective: Post-stroke epilepsy (PSE) is associated with increased morbidity and mortality. Stroke-associated acute symptomatic seizures are an important risk factor: 20.8-34.3% of these patients will go on to develop PSE. Identifying these ‘high risk’ individuals may result in earlier PSE diagnosis, treatment, and avoidance of seizure-related morbidity. This study was to identify predictors of PSE development in patients with stroke-associated acute symptomatic seizures. Participants and Methods: This was a retrospective cohort study of 167 patients with stroke-associated acute symptomatic seizures admitted to the Neurology Department of a tertiary Hospital of China, from 1 May 2006 to 30 January 2020. Both those with primary ischemic stroke and intracerebral hemorrhage were included in the study. Patient demographics, medical history, stroke-associated and seizure-related variables were evaluated with univariable analysis and multivariable Cox regression analysis. PSE was defined as unprovoked seizures occurring >7 days post-stroke. Data points were extracted from medical records and supplemented by tele-interview. Results: Of the 167 patients with stroke-associated acute symptomatic seizures, 49 (29.3%) developed PSE. NIHSS score >14 (hazard ratio [HR] 2.98, 95% CI 1.57-5.67), longer interval from stroke to acute symptomatic seizures (days 4-7 post-stroke) (HR 2.51, 95% CI 1.37-4.59) and multiple acute symptomatic seizures (HR 5.08, 95% CI 2.58-9.99) were independently associated with PSE development. This association remained in the sub-analysis within the ischemic stroke cohort. In the sub-analysis of the hemorrhagic stroke cohort, multilobar involvement (HR 4.70, 95% CI 1.47-15.06) was also independently associated with development of PSE. Further, we developed a nomogram to predict individual risk of developing PSE following stroke-associated acute symptomatic seizures. The nomogram showed a C-index of 0.73. Conclusion: More severe neurofunctional deficits (NIHSS score >14), longer interval from stroke to acute symptomatic seizures (days 4-7 post-stroke), and multiple acute symptomatic seizures were independently associated with development of PSE in patients with stroke-associated acute symptomatic seizures. This knowledge may increase clinical vigilance for development of PSE, facilitating rapid diagnosis and treatment initiation, and subsequently reduce seizure-related morbidity.